Ionotropic glutamate receptors in platelets: opposing effects and a unifying hypothesis. (17th November 2021) - Kalev-Zylinska, Maggie L.; Morel-Kopp, Marie-Christine; Ward, Christopher M.; Hearn, James I.; Hamilton, Justin R.; Bogdanova, Anna Y.
Abstract: Ionotropic glutamate receptors include α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR), kainate receptors (KAR), and N -methyl-D-aspartate receptors (NMDAR). All function as cation channels; AMPAR and KAR are more permeable to sodium and NMDAR to calcium ions. Compared to the brain, receptor assemblies in platelets are unusual, suggesting distinctive functionalities. There is convincing evidence that AMPAR and KAR amplify platelet function and thrombus formation in vitro and in vivo . Transgenic mice lacking GluA1 and GluK2 (AMPAR and KAR subunits, respectively) have longer bleeding times and prolonged time to thrombosis in an arterial model. In humans, rs465566 KAR gene polymorphism associates with altered in vitro platelet responses suggesting enhanced aspirin effect. The NMDAR contribution to platelet function is less well defined. NMDA at low concentrations (≤10 μM) inhibits platelet aggregation and high concentrations (≥100 μM) have no effect. However, open NMDAR channel blockers interfere with platelet activation and aggregation induced by other agonists in vitro ; anti-GluN1 antibodies interfere with thrombus formation under high shear rates ex vivo ; and rats vaccinated with GluN1 develop iron deficiency anemia suggestive of mild chronic bleeding. In this review, we summarize data on glutamate receptors in platelets and propose a unifying model that reconciles some of the opposing effects observed.